Distinct Properties and Structures Among B‐Crystalline Starch Granules. (21st December 2017) - Vamadevan, Varatharajan; Blennow, Andreas; Buléon, Alain; Goldstein, Avi; Bertoft, Eric
Abstract : Starch granules derived from certain tuber or root crops exhibit a B‐type polymorphic pattern and amylopectin with a high content of long B‐chains and comparatively long segments between the building blocks. Here, four B‐crystalline starches are selected to study their morphology and molecular composition, including lintnerization conducted at two different temperatures. The structure of the granules suggests that the B‐type crystalline starches can be divided into two distinct groups, with potato and edible canna forming one group having large granules with typical "growth rings" and the molecular structure of the lintners being dependent on the temperature of lintnerization. The other group consists of shoti and lesser yam starches possessing granules with alternating "granular slices" instead of rings or shells and the molecular composition of the lintners is not dependent on the temperature. It is found that the former group of starch possess lower gelatinization temperatures and swell at lower temperatures than the latter group, suggesting a more labile granular structure of potato and canna starches compared to shoti and lesser yam. As the properties are not related to the amylose or phosphate content of the granules, the result suggests that B‐crystalline starch granules are found as at least two distinct structural types with unique architectures. Abstract : Four B‐crystalline starches are selected to study their morphology and molecular composition including lintnerization conducted at two different temperatures. The results suggest that the B‐type crystalline starches can be divided into two distinct groups based on their structural and thermal properties.